The Right to a Fair Trial Under Article 6 ECHR During the Covid-19 Pandemic: - Andrzej Paduch (Central European Public Administration Review)
Purpose: The aim of the study is to analyse the possibility of modifying procedural law in the context of the legislative measures taken in connection with the COVID-19 pandemic on the example of the Polish administrative judiciary system. Design/Methodology/Approach: The study employs the dogmatic-legal method, analysing the provisions of the ECHR and examples of the regulation of administrative court proceedings in Poland. The interpretation of the provisions is carried out taking into account the jurisprudence of the courts, in particular the jurisprudence of the ECtHR. Findings: The study shows that no regulation taking away the right to have the case heard in public is compliant with the ECHR. Public hearing is in fact a crucial aspect of the right to a fair trial. However, in order to mitigate the effects of a pandemic, states may introduce such solutions which – within the limits of art. 6 sec. 1 ECHR – modify the law. Academic contribution to the field: The study suggests theoretical and general solutions to the problem that arose during the COVID-19 pandemic: whether and how certain aspects of the right to a fair trial can be limited without violating its essence. The issue is analysed from the perspective of the administrative judiciary and legal solutions adopted in Poland, but the conclusions may also apply to the regulations of other European countries and even to the civil or criminal judiciary. Practical Implications: The paper presents the requirements provided in art. 6 sec. 1 ECHR in the context of restrictions of public hearing implemented to counteract the spread of the COVID-19 pandemic. It may be a basis for further studies of the problem or for assessing the solutions adopted in the member states of the Council of Europe. Originality/Value: Publications concerning modifications to procedural law in the context of the COVID-19 pandemic are not numerous in scientific literature. Due to the lack of analyses, the paper will contribute to the development of literature.